2023
DOI: 10.1371/journal.pone.0294438
|View full text |Cite
|
Sign up to set email alerts
|

Differential vascular endothelial cell toxicity of established and novel BCR-ABL tyrosine kinase inhibitors

Yihua Wang,
Richard J. Travers,
Alanna Farrell
et al.

Abstract: BCR-ABL tyrosine kinase inhibitors (TKIs) have dramatically improved survival in Philadelphia chromosome-positive leukemias. Newer BCR-ABL TKIs provide superior cancer outcomes but with increased risk of acute arterial thrombosis, which further increases in patients with cardiovascular comorbidities and mitigates survival benefits compared to imatinib. Recent studies implicate endothelial cell (EC) damage in this toxicity by unknown mechanisms with few side-by-side comparisons of multiple TKIs and with no avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Our VCAM1 mRNA results are in line with the results of Huang et al, where TNF-α (10 ng/mL) significantly increased the VCAM1 expression at the protein level in HUVECs after 6 h of treatment [35]. Furthermore, our observation that the ponatinib-induced increase in the VCAM1 mRNA level is consistent with the result of an in vitro study at the protein level [36]. In addition, the same changes were observed at mRNA level by Paez-Mayorga et al [37]; however, they found augmented VCAM1 mRNA already after 24 h of ponatinib treatment in human aortic endothelial cell culture.…”
Section: Discussionsupporting
confidence: 92%
“…Our VCAM1 mRNA results are in line with the results of Huang et al, where TNF-α (10 ng/mL) significantly increased the VCAM1 expression at the protein level in HUVECs after 6 h of treatment [35]. Furthermore, our observation that the ponatinib-induced increase in the VCAM1 mRNA level is consistent with the result of an in vitro study at the protein level [36]. In addition, the same changes were observed at mRNA level by Paez-Mayorga et al [37]; however, they found augmented VCAM1 mRNA already after 24 h of ponatinib treatment in human aortic endothelial cell culture.…”
Section: Discussionsupporting
confidence: 92%